STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN BRAND AWARENESS CLASMILD - Raihan Ramadhan Ahmad Suhada; Fitri Norhabiba (Universitas Negeri Surabaya, 2025)
The rapid growth of the cigarette trade has triggered intense competition in both local and international markets. For more than twenty-three years, the brand awareness built by Clasmild has had a significant impact on its ability to compete. This study uses a descriptive qualitative approach to understand the phenomenon of consumer behavior, perspectives, motivations, and actions. The type of research method employed by the researcher is descriptive. Clasmild applies a marketing communication strategy using the four-ps of the marketing mix and the STP strategy to identify consumer characteristics, select the appropriate target market, and create competitive differentiation. Among the eight elements of the promotion mix, five key components are utilized to enhance brand awareness: Advertising, Personal Selling, Interactive Marketing, Sales Promotion, and Word of Mouth.